Structural semantic folktale model as a visualization means of structural and semantic relationships between Malaysian folktales' classes - Harun, Harryizman; Jamaludin, Zulikha (2017)
A study is conducted to preserve Malaysian folktales through a development of a Malaysian Folktale Classification System (MFCS) which is currently absent in Malaysia.The systematic classification system is developed by integrating three essential folktale unit: function, motif, and type.Such integration is necessary to ensure the classification system covers two significant aspects of a folktale which are structure/form and content/semantic.As a result of the integration, structural and semantic relationships are born, but they are embedded in the classification system.In order to visualize the duo-facet relationships, a network model coined as a Structural Semantic Folktale Model (SSFM) is constructed. The network model is a vital support and extension of the classification system because it permits deeper study to be conducted on the root of the Malaysian folktales collected.As an effort to visualize the model systematically, a computer assisted qualitative data analysis (CAQDAS) Atlas.ti is utilized.Being the emphasis of this article, it is hoped that the network model would provide a platform for understanding the core of one of Malaysia’s intangible cultural heritages and beckons deeper study on such connections.